ANALYSIS OF PRODUCTION AND INCOME OF CATFISH SALI BUSINESS IN KOTO MASJID VILLAGE, KAMPAR REGENCY RIAU PROVINCE - Hendrik, Hendrik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Catfish is one of the freshwater fish commodities that has fast growth and has high economic value. This fish is consumed in both fresh and processed form, where one of the processed fish that is in high demand is catfish sali. This research was conducted in Koto Masjid Village in December 2021. The purpose of the study was to determine the production, income and profits of the catfish sale business. The method used in this study is a survey method, data analysis is carried out by analyzing income and profits. Respondents in the study were catfish sali entrepreneurs, catfish cultivators, traders and community members who helped the broiler business. The results showed that the production of catfish sali has increased every year where in 2020 it increased by 3.64% compared to the previous year and in 2021 it increased by 32.4%. This situation causes the income and profits received by the catfish sali entrepreneurs to continue to increase along with the increase in the amount of production. The increase in profits was due to the increasing number of production while production costs did not increase.